(untitled) (Per Musi, 2013)
Traditional teaching methodologies of jazz and other popular music usually focus on homophonic improvisation. We propose a revision and adaptation of the tonal harmony theory by SCHOENBERG (1999, 2004) to create a basis for analysis, realization and composition of lead sheets.